The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cphc.201800452
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Photophysical Properties of Boron Heptaaryldipyrromethene Derivatives

Abstract: Increased interest has been devoted to the discovery of multifunctional materials with desirable properties, as continuous performance enhancement of various devices mainly depends on high-performance materials. Now, density functional theory has become a powerful tool to design new materials and rationalize experimental observations. In this work, we explored the photophysical properties origin of chiral boron heptaaryldipyrromethene (heptaaryl-BODIPY), which has charming optoelectronic properties. At the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Quantum chemistry can answer some of these questions by exploring the chemical and photochemical properties of BODIPY dyes, such as their luminescence spectra or the fluorescence/phosphorescence ratio. However, the most commonly used functionals applied within the framework of time-dependent density functional theory (TD-DFT) are not able to reproduce the photophysical properties of BODIPY dyes. , Several groups have overcome this difficulty by using other methods like SOS-CIS­(D) and CASPT2 , or using purpose-specific functionals. , These solutions are unfortunately not a panacea as SOS-CIS­(D) results rely on the quality of the underlying CIS calculation while CASPT2 requires an active space and suffers from the intruder state problem. Thus, an accurate theoretical method which is capable of delivering results of a uniform quality in a black box fashion and without such deficiencies is much desired for the study of larger molecules such as BODIPY compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemistry can answer some of these questions by exploring the chemical and photochemical properties of BODIPY dyes, such as their luminescence spectra or the fluorescence/phosphorescence ratio. However, the most commonly used functionals applied within the framework of time-dependent density functional theory (TD-DFT) are not able to reproduce the photophysical properties of BODIPY dyes. , Several groups have overcome this difficulty by using other methods like SOS-CIS­(D) and CASPT2 , or using purpose-specific functionals. , These solutions are unfortunately not a panacea as SOS-CIS­(D) results rely on the quality of the underlying CIS calculation while CASPT2 requires an active space and suffers from the intruder state problem. Thus, an accurate theoretical method which is capable of delivering results of a uniform quality in a black box fashion and without such deficiencies is much desired for the study of larger molecules such as BODIPY compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the density functional theory (DFT) was successfully applied to calculation of NLO properties of various derivatives, for example, carborane derivatives, organometallic complexes and so on [40][41][42][43][44]. Therein, the NLO properties of molecules that contain BODIPY section have been investigated by several groups [28][29][30][45][46][47]. For example, Misra [45] have reported a theoretical study of tuning second-order NLO response of a series of aryl-substituted boron-dipyrromethene dyes, manifesting incorporation of various D/A groups in the phenyl ring with BODIPY can affect the ICT process, ultimately alter the NLO properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Misra [45] have reported a theoretical study of tuning second-order NLO response of a series of aryl-substituted boron-dipyrromethene dyes, manifesting incorporation of various D/A groups in the phenyl ring with BODIPY can affect the ICT process, ultimately alter the NLO properties. Liu et al [46] have explored the NLO properties origin of chiral boron heptaaryldipyrromethene compounds with the aid of DFT calculations. The results indicated that the compounds with the large first hyperpolarizability values will to be the excellent candidates for the second-order NLO materials.…”
Section: Introductionmentioning
confidence: 99%